Relativism, suffering, and beyond : essays in memory of Bimal K. Matilal - Bilimoria, Purusottama; Matilal, Bimal Krishna; Mohanty, J. N. (Oxford University Press, 1997)
Contributed articles on Hindu and Buddhist philosophy. The essays in this collection were written by an international body of scholars in memory of Professor Bimal K. Matilal. They discuss Vedanta, Nyaya, and Buddhism; thematically they deal with problems of relativism, evil, suffering, emotions, and value judgement.